Restoring Murray River floodplain wetlands: Does the sediment record inform on watering regime? - Gell, Peter A. (River research and applications, 2020)
The floodplain wetlands of the southern Murray Darling Basin (MDB) have been subject to the impacts of catchment and water resource development for more than a century. Their current degraded state is attributed to the regulation of the rivers and ion of water volume for irrigation. The MDB Plan is to return at least 2,750 Gl of mean annual flow to the system to restore the condition of waterways. Considerable recent investment in infrastructure enables water to be released into the basin's floodplain wetlands. The proposed watering regime is underpinned by modelling that suggests that, before regulation, overbank flows would have occurred regularly as discharge peaked in winter and spring. Sediment cores have been extracted from over 50 floodplain wetlands of the southern Murray Basin. Those from several, large meander wavelength billabongs extend for 1,000–5,000 years suggesting that these sites were permanently inundated over that time. Others extend to ~200 years and are presumed not to have accumulated sediment until more recently. The records of most wetlands, however, only extend to the onset of river regulation in the 1920s, suggesting that before then they were not inundated for sufficient duration for net accumulation to occur. Preserved diatoms suggest that the shallow, plant‐dominated wetlands of the past have transitioned to deep, turbid water systems today. As rivers are identified as a source of sediment to wetlands, less regular inundation, rather than more, is a viable option in restoring the ecological function of these floodplain wetlands and in slowing sediment infill.